Assessment of the impact of emigration on the origin economy - Rita Remeikiene; Ligita Gaspareniene (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
Our article concentrates to the main aim - to assess the impact of emigration on an origin economy. This topic was chosen because the theoretical research has disclosed that the positive impact of emigration usually manifests through monetary transfers to a native country while the negative impact mainly emerges as a reduction in the labour force, which, in its turn, causes deterioration of a country's demographic and economic situation. It has been found that the growing flows of emigration significantly reduce Lithuanian population and cause "brain drain". High emigration rates also have a negative impact on Lithuanian national economy, in particular, its unemployment rate (the opposite effect). To reduce the rates of emigration from the country, Lithuania must develop and improve such ALPM's elements as combination of work and dual vocational training, targeted selection of the industries for arrangement of an apprenticeship, manual training, dual vocational training and workplace training, segmentation of the unemployed by the indications of employment impediment, individual work with the unemployed to restore their basic skills (motivation, practice, health improvement), vocational guidance of young people (students) and early involvement of students into the labour market by combining studies and work.
Keywords: J11; O15; 650; emigration; economics; macroeconomic indicators; Lithuania